2001
DOI: 10.1044/1092-4388(2001/040)
|View full text |Cite
|
Sign up to set email alerts
|

Voice Activity and Participation Profile

Abstract: Traditional clinical voice evaluation focuses primarily on the severity of voice impairment, with little emphasis on the impact of voice disorders on the individual's quality of life. This study reports the development of a 28-item assessment tool that evaluates the perception of voice problem, activity limitation, and participation restriction using the International Classification of Impairments, Disabilities and Handicaps-2 Beta-1 concept (World Health Organization, 1997). The questionnaire was administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(36 citation statements)
references
References 20 publications
1
28
0
7
Order By: Relevance
“…As in other studies [3,5,19], we also found a good correlation between the average scores from the subjective estimation of the voice and the total score of VHI-T, however with varying correlations between the diagnose groups. A discrepancy between VHI-T and VAS may be of interest since it may reflect the patient's attitude to his/her symptoms: a patient who has a combination of high VHI-T total score and a low value of self-estimation of the voice may in fact not value the symptoms as a big trouble while another individual with the reverse relationship between the self-estimation of the voice and VHI-T total values the symptoms as less tolerable.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As in other studies [3,5,19], we also found a good correlation between the average scores from the subjective estimation of the voice and the total score of VHI-T, however with varying correlations between the diagnose groups. A discrepancy between VHI-T and VAS may be of interest since it may reflect the patient's attitude to his/her symptoms: a patient who has a combination of high VHI-T total score and a low value of self-estimation of the voice may in fact not value the symptoms as a big trouble while another individual with the reverse relationship between the self-estimation of the voice and VHI-T total values the symptoms as less tolerable.…”
Section: Discussionsupporting
confidence: 90%
“…Correlations between the subjective estimations of the voice and the overall VHI-T score were reliable in the whole population but varied between the different diagnostic groups. Subjective estimation of voice is usually used only for proving the face validity of the VHI-questionnaire [3,5,19]. We choose to include this simple measure as a permanent item in the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of voice disorders on the participants’ daily communication, job, social communication, and emotional aspects was assessed using the Voice Activity and Participation Profile (VAPP) 32 , which is a 28-item questionnaire completed by the participants.…”
Section: Methodsmentioning
confidence: 99%
“…The participants made a self-assessment of their voice problems and voice-related quality of life by completing the Voice Activity and Participation Profile (VAPP) questionnaire (validation of the Finnish translation [39,40]). The total points of the questionnaire (28 questions on a visual analog scale of 10 cm, maximum score = 280, VAPP total score) were used to represent the participants' estimations of the severity of their voice impairment and its impact on quality of life.…”
Section: Methodsmentioning
confidence: 99%